A study on Extent of Participation and Perception of Farmers on Benefits of IWMP (Integrated Watershed Management Programme) - Vaithiyanath AO; G Samuel; I Sreenivasa Rao (Journal of Extension Education, 2019)
Watershed is a basin-like landform defined by highpoints and ridgelines that descend into lower elevations and stream valleys. Watershed development involves conservation, regeneration and judicious utilization of natural resources. It aims to bring about an optimum balance between the demand and use of natural resources so that they remain sustainable over time. Ex-post-facto research design was adopted for the study with the objective to find out the extent of participation of watershed farmers in Integrated Watershed Management Programme (IWMP) and to find out its benefits. Majority of the watershed farmers had medium level of participation in IWMP followed by low and high participation. The independent variables viz., age, education, farming experience, training received, socio-political participation, efficiency of group leadership, group cohesiveness, decision making pattern and hard work oriented-ness were found positively and significantly related with the extent of participation of watershed farmers in IWMP.